Chasmanthera dependens Root Extract as a Dietary Supplement: Impacts on Reproduction Biomarkers in Clarias gariepinus Broodstock - Ojetayo, Teslim Asafe; Durojaiye, Abiola Fadilat; Oshoke, Omolegho Justina (Department of Aquaculture, 2025)
This study investigated the effects of dietary supplementation with Chasmanthera dependens on the reproductive performance and histopathological health of Clarias gariepinus (African Catfish). A total of 75 healthy adult fish were randomly assigned to five dietary treatments: a control group with no additives and four groups receiving C. dependens at 10g, 20g, 30g, and 40g per kg of feed. The experimental duration lasted 90 days, during which parameters such as sperm quality, egg quality, and histopathological observations of gonads were assessed. Results indicated that the control group exhibited superior sperm quality, including the highest milt volume, motility, and live/dead ratio, compared to all treatment groups. Fecundity, egg size, fertilization rates, and hatchability percentages were also highest in the control group. Conversely, groups receiving higher levels of C. dependens demonstrated significantly lower (p<0.05) reproductive performance metrics, suggesting adverse effects linked to excessive supplementation. Histopathological analysis revealed no observable lesions in the testes and ovaries of the control and lower treatment groups, with healthy seminiferous tubules and advanced vitellogenesis. However, the group receiving the highest level of C. dependens exhibited signs of congestion in the ovaries, indicating potential detrimental effects. Overall, while C. dependens may offer reproductive benefits at moderate levels, excessive dietary inclusion negatively impacted sperm and egg quality as well as gonadal health. Further research is recommended to establish optimal inclusion rates for maximizing the beneficial effects of C. dependens while minimizing adverse impacts on reproductive health.